TRANSTORNOS ALIMENTARES NO GÊNERO MASCULINO: REVISÃO DA LITERATURA - MISTURA, CLAUDELÍ; RENCK, JOÃO S.; DIETZ, GRACIELE; HILDEBRANDT, LEILA M.; PIOVESAN, SOLANGE M. S. (Salão do Conhecimento, 2013)
Resumo